HUBUNGAN JARAK KELAHIRAN DAN JUMLAH ANAK DENGAN STATUS GIZI BALITA DI PUSKESMAS KAO KECAMATAN KAO KABUPATEN HALMAHERA UTARA - Karundeng, Lani Ribka; Ismanto, Amatus Yudi; Kundre, Rina (Universitas Sam Ratulangi, 2015)
ABSTRACT : Nutritional status was the ultimate result of the balance between food intake in the body with the nutrients the body needs it. Birth spacing and number of children who are too much will affect the nutritional status in the family. The purpose of this study was to determine the relationship of birth spacing and number of children with nutritional status of children in the health center Kao. The Design of this research was analytic survey with cross sectional approach. The sample totaled 246 respondents, sampling using Systematic Random Sampling technique. Results using Chi-Square on Continuity Correction with significance level Î± = 0.05 or 95%. The results of statistical tests spacing and nutritional status in getting p value = 0.000 and the number of children with nutritional status in getting p value = 0.90. The conclusion of this research is there was relationship between birth spacing and nutritional status and there was no association with nutritional status of children under five in the health center Kao, Kao District of North Halmahera. Recommended improve health services, especially outreach to the community, improving the quality and quantity of health personnel and working closely with village officials in providing an understanding of the norms and customs related to birth spacing and number of children with nutritional status of children. Key words: Space Birth, Number of Children, Nutritional Status ABSTRAK : Status Gizi merupakan hasil akhir dari keseimbangan antara makanan yang masuk dalam tubuh dengan kebutuhan tubuh akan zat gizi tersebut. Jarak kelahiran dan jumlah anak yang terlalu banyak akan mempengaruhi status gizi dalam keluarga. Tujuan penelitian ini adalah untuk mengetahui hubungan jarak kelahiran dan jumlah anak dengan status gizi balita di Puskesmas Kao. Desain Penelitian bersifat survey analitik dengan pendekatan Cross Sectional. Sampel berjumlah 246 responden, pengambilan sampel menggunakan tehnik Systematic Random Sampling. Hasil Penelitian menggunakan uji Chi-Square pada Continuity Correction dengan tingkat kemaknaan Î± = 0,05 atau 95 %. Hasil uji statistik jarak kelahiran dengan status gizi di dapatkan nilai p value = 0,000 dan jumlah anak dengan status gizi di dapatkan nilai p value = 0,90. Kesimpulan yaitu ada hubungan jarak kelahiran dengan status gizi dan tidak ada hubungan jumlah anak dengan status gizi balita di Puskesmas Kao Kecamatan Kao Kabupaten Halmahera Utara. Rekomendasi meningkatkan pelayanan kesehatan terutama penyuluhan kepada masyarakat,meningkatkan mutu dan jumlah tenaga kesehatan dan bekerja sama dengan aparat desa dalam memberikan pemahaman tentang norma dan adat istiadat terkait jarak kelahiran dan jumlah anak dengan status gizi balita. Kata Kunci : Jarak Kelahiran, Jumlah Anak, Status Gizi